SELF-ASSESSMENT OF LANGUAGE SKILLS AND EVALUATION OF PERFORMANCE IN ENGLISH FOR SPECIFIC PURPOSES CLASSROOMS - Darginaviciene, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Although evaluation has been increasingly used in education for a long time, attention to evaluation and its uses in English language teaching is relatively recent. Essentially, evaluation may be carried out to determine if the students achieved a certain level of language proficiency. Recently self-evaluation of language skills has been used to find out how students assess their accomplishments in language learning. On the other hand, formal testing is the most common way to measure achievement and proficiency in language learning that teachers conduct during an academic year. Formal testing is considered to be an effective tool that can help teachers identify students’ strengths and weaknesses and evaluate the effectiveness of teaching. This article focuses on student’s perceptions of success in learning English for Specific Purposes (ESP) and formal evaluation of their performance in class activities. The methods of the research include the administration of the designed questionnaire, analysis of students’ responses and their statistical treatment by a means of the Statistical Package for Social Sciences (SPSS 19). The self-evaluation data are compared with the results of formal testing. The conclusions are drawn on the merits of self-evaluation in learning ESP.